2016
DOI: 10.1111/jgs.14449
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as a Modifiable Risk Factor for Dementia: A Nationwide Population‐Based Cohort Study

Abstract: Periodontitis is associated with greater risk of developing dementia. Periodontal infection is treatable, so it might be a modifiable risk factor for dementia. Clinicians must devote greater attention to this potential association in an effort to develop new preventive and therapeutic strategies for dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
107
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 36 publications
4
107
1
Order By: Relevance
“…These results are consistent with our findings. Our results are also consistent with the ones reported by Lee and co‐workers (Lee et al., ) demonstrating that individuals with periodontitis had a higher risk of developing dementia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with our findings. Our results are also consistent with the ones reported by Lee and co‐workers (Lee et al., ) demonstrating that individuals with periodontitis had a higher risk of developing dementia.…”
Section: Discussionsupporting
confidence: 93%
“…In a retrospective case–control study, a modest higher risk for dementia was reported among individuals with periodontitis after adjustment for sociodemographic characteristics and comorbidities (Lee et al., ). In a 3‐year follow‐up study, a twofold higher risk for cognitive decline was reported for individuals with severe periodontitis compared to individuals without periodontitis (Iwasaki et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in agreement with recent findings from epidemiological studies reporting a significant association between periodontitis and cognitive impairment, although very few of these studies involved detailed clinical evaluations of periodontal status. One strength of the current study is that we used data from full‐mouth assessments of periodontal status involving examinations of six sites on all teeth, allowing us to define periodontitis by two commonly used case definitions as well as calculate PISA.…”
Section: Discussionsupporting
confidence: 93%
“…A putative link between periodontitis and cognitive impairment/dementia has been reported . There are several possible underlying mechanisms for this association.…”
Section: Introductionmentioning
confidence: 99%
“…Increased risk among patients with periodontitis of cardiovascular disease, pneumonia, dementia, Alzheimer's disease progression, osteoporosis, periprosthetic infection and gastric infection have been previously reported. In addition, periodontitis has also been reported to affect several liver diseases, such as hepatocellular carcinoma, cirrhosis, non‐alcoholic fatty liver disease and even liver transplantation .…”
Section: Discussionmentioning
confidence: 93%